Complex Networks VII Proceedings of the 7th Workshop on Complex Networks CompleNet 2016 - Cherifi, Hocine; Gonçalves, Bruno; Menezes, Ronaldo; Sinatra, Roberta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The last decades have seen the emergence of Complex Networks as the language with which a wide range of complex phenomena in fields as diverse as Physics, Computer Science, and Medicine (to name just a few) can be properly described and understood. This book provides a view of the state of the art in this dynamic field and covers topics ranging from network controllability, social structure, online behavior, recommendation systems, and network structure. This book includes the peer-reviewed list of works presented at the 7th Workshop on Complex Networks CompleNet 2016 which was hosted by the Université de Bourgogne, France, from March 23-25, 2016. The 28 carefully reviewed and selected contributions in this book address many topics related to complex networks and have been organized in seven major groups: (1) Theory of Complex Networks, (2) Multilayer networks, (3) Controllability of networks, (4) Algorithms for networks, (5) Community detection, (6) Dynamics and spreading phenomena on networks, (7) Applications of Networks.
Theory of Complex Networks -- Multilayer Networks -- Controllability of Networks -- Algorithms for Networks -- Community Detection -- Dynamics and Spreading Phenomena on Networks -- Applications of Networks.
Keywords: Computational intelligence; Graph theory; Artificial intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Graph Theory; Artificial Intelligence; Applied Dynamical Systems